Evaluación de la capacidad del floculante A y B en el control de parámetros fisicoquímicos durante el proceso de dewatering del campo X para la formulación de un nuevo lodo de inicio base agua a nivel de laboratorio (2021)
The dewatering process is of utmost importance for the drilling part due to the fact that it separates the solid phase from the continuous phase of the discarded mud, thus ensuring optimal disposal. For this reason, research is carried out where the performance of three polymers, A, B and Lipesa 1641, is compared, the latter used by the company HOLSAN SAS for the dewatering process in field X. The evaluation of polymers It is carried out by means of a jar test which seeks to simulate the dewatering process, therefore, variations of concentrations are made at 5%, 10%, 15% and 20%, RPM of 40, 60, 80 and 100 and shaking times of 40 minutes, 60 minutes and 80 minutes. After completing the jar test process, the resulting water is evaluated with the tests of suspended solids, sulfate content and finally chloride content to determine if it meets the parameters established by resolution 0631 of 2015 (article 11) for the discharge of waters. After the end of the polymer evaluation stage, the formulation of a starting sludge begins, ideal for the 17 ½ ”section with the water resulting from dewatering. To this mud is added 17 g of bentonite for every 350 mL of water and 0.1 g of caustic soda for every 350 ml of water. Once the sludge formulation process is finished, physical and chemical tests are carried out to determine if it is classified as starting sludge according to its properties and the parameters established for a spud mud.